Optimalisasi Pendampingan Shadow Teacher dalam Proses Adaptasi Siswa ADHD di Sekolah Inklusi - Syailil Aliyah; Nova Estu Harsiwi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Inclusive education seeks to ensure equal learning opportunities for all students, including those with special needs such as Attention Deficit Hyperactivity Disorder (ADHD). Students with ADHD often struggle with concentration, self-regulation, and social interaction, which can hinder their ability to thrive in mainstream classroom settings. As a result, the role of a shadow teacher as a personal aide becomes crucial. This article explores effective strategies to support students with ADHD through the involvement of shadow teachers in an inclusive educational environment, with a specific focus on SD Muhammadiyah Manyar Gresik. Using a qualitative descriptive approach, the study highlights various forms of support—academic assistance, behavioral intervention, and socio-emotional guidance—while emphasizing the importance of collaboration among shadow teachers, classroom educators, and parents. Data were gathered through interviews, observations, and document analysis. The results suggest that skilled and well-supported shadow teachers play a significant role in helping students with ADHD adjust to and succeed in inclusive learning setting.